Suicide in the COVID-19 Pandemic - Ni Nyoman Gita Kharisma Dewi; Ida Aju Kusuma Wardani (Jurnal Psikiatri Surabaya, 2023)
Introductions: The COVID-19 pandemic affects various aspects of life, not only in terms of health but also economically and socially. Several studies have shown that the impact of the COVID-19 pandemic is related to an increase in the number of suicides. The study review aims to determine the incidence of suicide during the COVID-19 pandemic. Methods: This study review was compiled using the literature review method by collecting sources from valid scientific literature, namely PubMed and Scientific Direct. Discussions: Suicide risk is related to several factors due to the COVID-19 pandemic, such as a significant relationship between suicide and living in an area with a high prevalence of COVID-19 infection, loss of income due to the pandemic, having relatives or acquaintances who died from COVID-19, fear of being infected by COVID-19, and changes in the learning system. Things that can be protective factors include mental health knowledge, exercising regularly during the pandemic, family support, and a high level of awareness and preventive measures for COVID-19. Conclusions: The COVID-19 pandemic also affects mental health. The impact of the COVID-19 pandemic has a relationship with increased suicides.